Reliability analysis on ethics practice survey in Malaysia context: a preliminary study - Mat Rani, Nurul Hasyimah; Wan Jaafar, Wan Marzuki; Mohd Matore, Mohd Effendi @ Ewan (Human Resource Management Academic Research Society, 2016)
The aim of this paper is to disseminate findings related to the reliability of the instruments to measure the ethics practice of counsellor in Malaysia. The instrument was developed by Kenneth S Pope (1987) and it consisted of 88 items. Based on the pilot study, Cronbach’s Alpha yield at .88 for ethical behaviour and .992 for ethics belief. The instrument was involved 108 registered and non-registered counsellors in Malaysia. The finding demonstrates that the instrument is suitable to measure ethics practice among counsellor.